2010
DOI: 10.4081/ijas.2010.e35
|View full text |Cite
|
Sign up to set email alerts
|

Use of injectable transponders for the identification and traceability of pigs

Abstract: Individual identification in pigs is a key point for management, traceability and trade control. The aim of this experiment was to study retention rate and functionality of electronic identification systems in pigs, injected in different sites, to evaluate traceability of animals and highlight histopathological alterations of tissues in different inoculation sites. A total of 60 crossbred piglets were used to compare different transponder inoculation sites. One group (15 piglets) was identified only by plastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…The application of the ear tag is a rather simple operation and can be done by the farmer without risks for the animal. In literature, Stärk et al (1998) and, recently, Prola et al (2010) reported a readability of 100% for electronic ear tags in pigs; in contrast, Babot et al (2006) obtained a similar readability (96.7%) to the one observed in our trial. The reading shows a percentage of error of 0.1%, however, problems may rise as ear tags are subject to a high loss rate, up to 40% (Caja et al, 2004).…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…The application of the ear tag is a rather simple operation and can be done by the farmer without risks for the animal. In literature, Stärk et al (1998) and, recently, Prola et al (2010) reported a readability of 100% for electronic ear tags in pigs; in contrast, Babot et al (2006) obtained a similar readability (96.7%) to the one observed in our trial. The reading shows a percentage of error of 0.1%, however, problems may rise as ear tags are subject to a high loss rate, up to 40% (Caja et al, 2004).…”
Section: Resultssupporting
confidence: 72%
“…Different performances could be explained by technical characteristics of ear tags (weight, shape, materials, etc.) that influBarbieri et al (Lambooij and Merks, 1989;Stärk et al, 1998) obtained a lower readability, while Prola et al (2010) reported the same percentage, as summarized in Table 3. One of the most important parameters for evaluating the suitability of an identification system for field use is the time needed for its application.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…In this study, a large number of microchips were lost from the auricle base during the first month after injection, confirming previous findings (Caja et al, 2005;Prola et al, 2010). A possible reason for this unacceptably large loss of microchips could be the size of the needle used for injection, which could have allowed the microchip to fall out before the skin had healed (Caja et al, 2005).…”
Section: Discussionsupporting
confidence: 88%
“…A transponder that is deposited close to the point of application is likely to be lost after application (Caja et al 2005). Perineal transponders are difficult to recover in heavy pigs, and incisions to remove them at slaughter could compromise carcass quality (Prola et al 2010). Intra-peritoneal application is perceived to be easy to apply (Marchi et al 2007); Caja et al (2005) found transponder application at the intra-peritoneal location (took 84.3 s) to take less time than that done at the auricle base which was more time consuming (101.7 s).…”
Section: Animal Identification Methodsmentioning
confidence: 99%